Charge transfer of cocrystal complex featuring efficient aggregation-induced emission and self-powered photo-electrochemical photodetector. (February 2023) - Yang, Xiao-Gang; Zhang, Ji-Rui; Guo, Jia-Hui; Ma, Cheng-Yu; Tian, Xu-Ke; Dou, Chang-Xun
Abstract: A novel cocrystal complex CZIPA-AD assembled by twisting D-A molecule 5-(9 H -carbazol-9-yl)isophthalic (CZIPA) and acridine (AD) through a facial solution volatilization process is reported. The combination of photophysical investigation and DFT analysis verify a reasonable cooperation of hybridized local and charge transfer (HLCT) and aggregation-induced emission (AIE) character. The orbital overlap on CZIPA (for local excited (LE) state) and orbital spatial separation between CZIPA and AD (for charge transfer (CT) state) satisfy the formation of HLCT character. The presence of AD molecules preclude the formation of π-stacking between the carbazole halves, preventing the quenching of PL emission in the aggregate state. It shows intense orange emission in aggregated solid state with high PLQY of 80% and prolonged PL lifetime of 38.57 ns. A self-powered photo-electrochemical photodetector fabricated from the cocrystal thin film exhibits a remarkable detectivity (4.78 × 10 10 Jones) in neutral aqueous solution, which is at lest one order of magnitude higher than other reported inorganic materials measured in alkaline solution with additional bias potential. Graphical abstract: Image 1 Highlights: One cocrystal complex CZIPA-AD was synthesized by the assembly of twisting D-A molecule 5-(9H-carbazol-9-yl)isophthalic (CZIPA) and acridine (AD) under a facial solution volatilization process. CZIPA-AD shows the cooperation of aggregation-induced emission (AIE) and hybridized local and charge transfer (HLCT) character verified by the combination of photophysical investigation and DFT analysis. It emits intense orange emission in aggregated solid state with high PLQY of 80% and prolonged PL lifetime of 38.57 ns. Photoelectric measurements reveal remarkable detectivity (4.78 × 1010 Jones) of the cocrystal thin film, which is at lest one order of magnitude higher than other reported inorganic materials.